Evaluasi Ketahanan Gempa pada Fondasi Tangki Minyak 3000 bbl Berdasarkan Metode Analitik dan Elemen Hingga - Rosi Nursani; Fitriana Sarifah; Hidayanto (Jurnal Manajemen Teknologi & Teknik Sipil, 2023)
Oil tank buildings are designed to be earthquake-resistant throughout their lifetime. The foundation of the 3000 bbl petroleum storage tank in Penukal Abab Lematang Ilir (PALI) Regency has been designed using previous seismic standards. This encourages the importance of evaluating foundation resilience against the latest standards because the latest standards show an increase in the Peak Ground Acceleration value. This research aims to determine the Safety Factor (FK) and settlement of the existing foundation of a 3000 bbl petroleum storage tank at the Collecting Station in PALI Regency using earthquake parameters in 2022. A quantitative approach was carried out using finite element and analytical analysis. Steel tank structure design, soil investigation, loads, earthquake parameters, and existing foundation design are used. FK and settlement results will be evaluated based on API 650 and SNI 8604:2017 requirements. The analytical and finite element research results show that the FK value meets the requirements. However, the FK value obtained tends to be too large compared to the requirements. Therefore, it is recommended to design a foundation size smaller than the existing foundation as an efficiency measure. Apart from that, the settlement results at the end of the service life (50th year) show that it is still within the settlement limit permitted by API 650. The research results have confirmed that the existing foundation can withstand earthquakes based on earthquake parameters in 2022. So, these results can be used to develop tank foundation designs for earthquake-safe oil storage in similar locations.